1994
DOI: 10.1016/1044-0305(94)85068-2
|View full text |Cite
|
Sign up to set email alerts
|

Tandem mass spectrometry of poly(ethylene glycol) lithium-attachment ions

Abstract: A study of the fast-atom bombardment tandem mass spectrometry behavior of a number of ethylene glycol polymers (PEGs) has been carried out. Both linear (hydroxyl, amino, and/or alkyl end groups) and cyclic (crown ether) polymers were studied. One of the materials is a block copolymer of ethylene and propylene oxides. Collisional activation was carried out in the collision octapole of a BEoQ hybrid mass spectrometer at a translational energy of 50 eV, with collision gas air. For the linear polymers, the most in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
100
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 13 publications
7
100
0
Order By: Relevance
“…For example, while dissociation of protonated poly(methyl methacrylate) (PMMA) was shown to proceed via charge-induced eliminations of methanol from the pendant ester groups [4], alkali-cationized PMMA mainly dissociates to yield low-mass radical ions carrying one of the original chain ends, according to charge-remote mechanisms [5][6][7][8]. Within the same class of metals, the nature of the adducted cation can also influence MS/MS results, as shown in the case of poly(ethylene glycol) for which dissociation of lithiated molecules generates polymeric product ions after internal backbone cleavages or rearrangements, whereas a bare alkali cation was often the only reported product ion arising from dissociation of sodium or potassium adducts [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, while dissociation of protonated poly(methyl methacrylate) (PMMA) was shown to proceed via charge-induced eliminations of methanol from the pendant ester groups [4], alkali-cationized PMMA mainly dissociates to yield low-mass radical ions carrying one of the original chain ends, according to charge-remote mechanisms [5][6][7][8]. Within the same class of metals, the nature of the adducted cation can also influence MS/MS results, as shown in the case of poly(ethylene glycol) for which dissociation of lithiated molecules generates polymeric product ions after internal backbone cleavages or rearrangements, whereas a bare alkali cation was often the only reported product ion arising from dissociation of sodium or potassium adducts [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Dissociation pathways have been studied for a large variety of polymers, such as PEO [11][12][13][14][15][16][17][18][19][20][21][22][23][24], PS [20,[23][24][25][26][27][28][29][30], or poly(methylmethacrylate) (PMMA) [20, 21, 23, 30 -32]. In contrast, few MS studies have been reported for PMAA and most of them focused on the analysis of volatile thermal degradation products of the polymer [33,34].…”
mentioning
confidence: 99%
“…Our previous study was focused on alcohol ethoxylates whose end-groups are linked to polyglycol chains via ether-type C™O bonds (i.e., polyglycol ethers). The results generated therein were compared to earlier studies of the same type of polyglycols employing fast atom bombardment (FAB) MS/MS by Latimer and coworkers [22][23][24][25].Poly(ethylene glycol) ester, especially fatty acid methyl ester ethoxylate (FAMEE), is another class of polyglycol which can be used as an alternative to alcohol ethoxylates in many industrial applications. With varying alkyl chain lengths in the fatty acid moiety, a wide range of hydrophilic lipophilic balance (HLB) values can be achieved to suit different applications [14].…”
mentioning
confidence: 99%
“…Our previous study was focused on alcohol ethoxylates whose end-groups are linked to polyglycol chains via ether-type C™O bonds (i.e., polyglycol ethers). The results generated therein were compared to earlier studies of the same type of polyglycols employing fast atom bombardment (FAB) MS/MS by Latimer and coworkers [22][23][24][25].…”
mentioning
confidence: 99%